Atomic‐Level Quality Assessment of Enzymes Encapsulated in Bioinspired Silica. Issue 1 (2nd December 2015) - Martelli, Tommaso; Ravera, Enrico; Louka, Alexandra; Cerofolini, Linda; Hafner, Manuel; Fragai, Marco; Becker, Christian F. W.; Luchinat, Claudio
Abstract: Among protein immobilization strategies, encapsulation in bioinspired silica is increasingly popular. Encapsulation offers high yields and the solid support is created through a protein‐catalyzed polycondensation reaction that occurs under mild conditions. An integrated strategy is reported for the characterization of both the protein and bioinspired silica scaffold generated by the encapsulation of enzymes with an external silica‐forming promoter or with the promoter expressed as a fusion to the enzyme. This strategy is applied to the catalytic domain of matrix metalloproteinase 12. Analysis reveals that the structure of the protein encapsulated by either method is not significantly altered with respect to the native form. The structural features of silica obtained by either strategy are also similar, but differ from those obtained by other approaches. In case of the covalently linked R5–enzyme construct, immobilization yields are higher. Encapsulation through a fusion protein, therefore, appears to be the method of choice. Abstract : Structure capture : Enzymes encapsulated in silica by an external silica‐forming promoter—or with the promoter fused to the enzyme—can be characterized using an integrated NMR strategy to monitor both the protein and the silica scaffold (see figure).